CD70 in Thymic Squamous Cell Carcinoma: Potential Diagnostic Markers and Immunotherapeutic Targets - Kashima, Jumpei; Hishima, Tsunekazu; Okuma, Yusuke; Horio, Hirotoshi; Ogawa, Masumi; Hayashi, Yukiko; Horiguchi, Shin-ichiro; Motoi, Toru; Ushiku, Tetsuo; Fukayama, Masashi (Frontiers in Oncology, 2022)
CD70 – a ligand protein of CD27 on lymphocytes – is expressed in a large spectrum of malignancies. It is an attractive target for antibody-based therapy and several clinical trials are currently being conducted. However, there is no evidence regarding the expression of CD70 and its relationship with expression of programmed death ligand-1 (PD-L1) and CD27+ tumor-infiltrating lymphocytes (TIL) in formalin-fixed paraffin-embedded (FFPE) tissues of thymic tumors. FFPE tissues of thymic squamous cell carcinoma (TSCC) (operative specimens, n = 31; biopsy specimens, n = 11), thymoma (n = 60), thymic carcinoid (n = 3), and lung squamous cell carcinoma (LSCC) (n = 30) were analyzed immunohistochemically. Immunoreactivity for CD70 was semi-quantitatively scored according to the proportion of positive tumor cells. Moreover, the densities of CD27-positive intratumoral TIL (iTIL) and stromal TIL of TSCC were assessed and survival was compared. Most TSCC cases (87%; 27/31) were CD70-positive. In contrast, all thymoma and thymic carcinoid cases were CD70-negative. In LSCC cases, CD70-positivity was significantly lower than TSCC cases (20%; 6/30). Biopsy and resected specimens obtained from the same patients demonstrated a consistent staining pattern (6/6 patients). The proportion of CD70-positive TSCC was comparable with those of CD5 (87%) and CD117 (90%). Correlation between CD70 and PD-L1 expression score was observed. There was no significant difference in survival between the CD70-high and CD70-low expression groups. Meanwhile, patients with CD27-positive iTIL-high tumors exhibited better survival than those with iTIL-low tumors. This tendency was weaker in the CD70-high subset. CD70 immunohistochemistry is useful in diagnosing TSCC. CD70 may prevent anti-tumor immunity via CD27. Immunotherapy targeting the CD70–CD27 axis may be a promising option for the treatment of TSCC.